Pemeriksaan Kerusakan Pompa Vakum menggunakan Analisa Getaran - Nurbaiti Nurbaiti (MAJALAH TEKNIK SIMES, 2019)
The research about vibration is used to find the type of vacuum pump damage 161V21 Plant Fatty Acid. This research was conducted in company that is process CPKO (Crude Palm Kernel Oil) into fatty alcohol. This company use rotating equipment in production process. When the process happen, engines fails due to excessive vibration. To make engine work properly, maintenance is done by analysis vibration to give information about engine damage type. Vibration analysis is done based on characteristic engine damage type that is see the domain frequency which is produced by fluke so that it can identify the damage type. Object in this research are vacuum pump 161V21 and vibration measure that is used in four location of bearing. The result of indication vibration damage by vacuum pump 161V21 are bearing first angular misalignment, second bearing that is indicate misalignment and coupling problem, Third bearing not yet identification the damaged, fourth bearing indicate mechanical looseness, misalignment and coupling problem. Actual problem are damage in the rubber and pump shaft which is corrosion happen because of rubbing against with inner bearing.